Strengthening Indonesia's Customs Enforcement Against Transnational Environmental Crime: A Comprehensive Policy Framework for Green Customs Implementation - Jatmiko Cahyoputro Utomo (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Transnational environmental crimes, including illegal wildlife trade, hazardous waste smuggling, illegal logging, and illicit timber trade, pose significant challenges for Indonesia as an archipelagic country strategically positioned within global trade routes. Following China’s 2017 ban on waste imports, Indonesia experienced a substantial surge in illegal waste shipments, leading to severe environmental, public health, and social consequences. As the primary border enforcement authority, the Directorate General of Customs and Excise plays a critical role in addressing these challenges, yet its effectiveness is constrained by structural and operational limitations. This study aims to examine enforcement gaps within Indonesia’s customs system in combating transnational environmental crime and to propose a comprehensive policy framework for the implementation of green customs. The research adopts a policy-based qualitative approach through a systematic review of peer-reviewed literature, international best practices, and global regulatory frameworks such as the Basel Convention and CITES. The findings reveal persistent challenges, including fragmented inter-agency coordination, limited detection technologies, underdeveloped intelligence systems, and insufficient human resource capacity. Based on these findings, the study proposes a phased green customs implementation framework emphasizing institutional reform, risk-based technological integration, capacity building, and enhanced ASEAN regional cooperation. The proposed framework is expected to strengthen border control effectiveness, reduce environmental harm, and support sustainable and secure international trade governance in Indonesia.